2020
DOI: 10.25259/cjhs_13_2020
|View full text |Cite
|
Sign up to set email alerts
|

Comparative sonographic evaluation of placental thickness in pregnancy-induced hypertension and normotensive pregnant women in the University of Calabar Teaching Hospital, Calabar, Nigeria

Abstract: Objectives: The human placenta is the nourishing reservoir for the sustenance of the fetus and synthesizes a growth-stimulating hormone to enhance proper growth and maturation. The size or thickness of the placenta enlarges as the pregnancy progresses in age to attain a favorable state which can cope with the increasing fetal demands. Placental thickness (PT) is a reflector of fetal well-being, and it is related to fetal weight making it necessary to assess the influence of pregnancy-induced hypertension (PIH)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
1
0
Order By: Relevance
“…In the presence of maternal hyperuricemia, the weight of the fetus reduces but our study did not reveal this pattern. This could possibly be due to the effect of a high maternal BMI (Efanga and Akintomide, 2020). Rather a significant positive relationship between maternal serum uric acid and EFW (p = 0.046) showed that the fetal weight appreciates as serum uric acid increases.…”
Section: Discussionmentioning
confidence: 95%
“…In the presence of maternal hyperuricemia, the weight of the fetus reduces but our study did not reveal this pattern. This could possibly be due to the effect of a high maternal BMI (Efanga and Akintomide, 2020). Rather a significant positive relationship between maternal serum uric acid and EFW (p = 0.046) showed that the fetal weight appreciates as serum uric acid increases.…”
Section: Discussionmentioning
confidence: 95%
“…The four sonographic measurements were summed to obtain the AFI in cm. Oligohydramnios refers to an amniotic fluid index below 5cm (Efanga et al, 2023). The measured value of AFI for each subject was recorded as data for this study.…”
Section: Methodsmentioning
confidence: 99%
“…The plane of measurement of the placental thickness is a perpendicular line drawn from the point of insertion of the umbilical cord at the chorionic membrane of the echogenic placenta to its basal membrane. This measurement is usually done during periods of maternal relaxation and the absence of myometrial contractions (Efanga and Akintomide, 2020). The measured value of the placental thickness for each subject was recorded as data for the study.…”
Section: Methodsmentioning
confidence: 99%